Development, Implementation And Analysis Of Direct Integration Offline Method In Wire Bonding - Lee, Foo Yeong (2011)
In this work, a wire bonding path creation method using computer-aided design information is developed to support the wire bonding process. This method is named as Direct Integration Offline Programming (Di-OLP). The Di-OLP utilizes numerical coordinate data extracted from bonding diagram creation software instead of commercial CAD application to generate the bonding path component of the wire bonding program.